Translation Quality Assessment: Linguistic Description versus Social Evaluation - House, Juliane (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2001)
Abstract The paper first reports on three different approaches to translation evaluation which emanate from different concepts of “meaning” and its role in translation. Secondly, a functional-pragmatic model of translation evaluation is described, which features a distinction between different types of translations and versions, and stresses the importance of using a “cultural filter” in one particular type of translation. Thirdly, the influence of English as a worldwide lingua franca on translation processes is discussed, and finally the important distinction between linguistic analysis and social judgement in translation evaluation is introduced, and conclusions for the practice of assessing the quality of a translation are drawn.